Comparison of ABTS and DPPH assays in estimating the total antioxidant capacity of lemongrass (Cymbopogon citratus) leaves - Sabocojan, Clarence D. (College of Home Economics, University of the Philippines Diliman, 2017)
This study compared the ABTS and DPPH assays in estimating the antioxidant capacity of methanolic extracts of lemongrass Cymbopogon citratus leaves obtained from a local market in Metro Manila, Philippines. The total phenolic content TPC was evaluated using the FolinCiocalteau method and was calculated to be 67.28 1.72 mg GAE100 g dw. The validated ABTS and DPPH assays were determined to be linear r2 0.95, with acceptable degrees of accuracy 80120 recovery and precision RSD 5. The Total Antioxidant Capacity TAC values obtained were also greater than the estimated limit of detection LOD and limit of quantitation LOQ, indicating that the results were accurate and precise. TAC was estimated using ABTS and DPPH assays, expressed in terms of Trolox Equivalents TE and Scavenging Activity SA. Significantly different p0.05 values were obtained between the assays, with significantly higher results for SA ABTS, and significantly higher TE for DPPH assay. Differences in results were attributed to variations in sample preparation and the unique mechanisms involved in each assay. Significant correlation was also determined between the ABTS SA r0.742, p0.05 and TPC. No linear correlation was observed between the TAC values measured using ABTS and DPPH assays. Caution should be applied when interpreting results due to the complex reactions involving antioxidants. Additionally, procedures should be validated prior to use in order to ensure its appropriateness when applied to a new sample matrix.